Examination of the neuromechanical factors contributing to golf swing performance - Sheehan, W. B.; Watsford, M. L.; Pickering Rodriguez, E. C. (Journal of Sports Sciences, 2019)
This study investigated the relationship between a range of neuromechanical variables in the lower- and upper-body, and golf performance. Participants were assessed for individual muscle stiffness, vertical stiffness (Kvert), flexibility, power and maximal isometric strength. Furthermore, golf performance was determined by handicap and club head speed. Pearson`s correlations quantified the relationships between neuromechanical variables and performance measures. Participants were also separated into relatively high club head speed (HC) and low club head speed (LC) groups and compared for physical characteristics. Club head speed showed positive relationships with Kvert and power and a negative relationship with hip mobility. The HC group exhibited superior Kvert and power, while strength and flexibility measures were not related to performance. Higher levels of lower-body stiffness, rate of force development and power output appear to be beneficial for generating superior club head speed. A stiffer system may reduce the time needed to remove the "slack" from the series elastic component therefore, reducing electromechanical delay and enhancing rate of force development. The large positive association with rate of force development suggests that increasing this component, along with power production may be superior focal components for training in golfers due to the short duration of the downswing.